Oficina Pedagógica: necessidades e objeto da atividade em contradição - Silva, Rosineide Albuquerque da (2006)
This thesis investigates the in-service education provided by the São Paulo State Educational Department to educational professionals. The research discusses the contradictions between the object constructed in one videoconference and the needs stated by the subjects within the education activity provided in the Pedagogical Workshop which took place during the educational program entitled Ensino Médio em Rede [High Schooling in a Network]. This is a program for Technical-Pedagogical Assistants, Coordinators and Teachers that work in the high school context. The present study is founded on the Socio-Historical-Cultural Activity Theory (Vygotsky, 1934/2000, Leontiev, 1977/2003 & Engeström, 1999), which allows for the teacher educational activity to be seen as a whole, so as to provide a better understanding of its object and needs. The study also embarks upon a critical teacher education, based on Freire s discussions (1970/ 1972/ 1992/ 1996/1997/1999/ 2001) as well as those of his followers. The methodology used in this research is one of a critical collaborative perspective, as discussed by Magalhães (1992b/1996a/2002/2003/2004), who defends that participants should have voice to critically and collaboratively construct their actions. Data was collected by means of videoconferences and recorded meetings in a Pedagogical Workshop which took place in a Regional Teaching Directorate within the State of São Paulo, in the first semester of 2005. These data were analyzed and discussed by means of the concepts of general text plan, thematic content and turn-taking (Bronckart, 2003) whose aim is to define the group of information revealed by the text so as to provide understanding of the meeting and of the videoconference as to the object constructed and the needs stated by the subjects involved in the activity. Results indicate that there has been a contradiction between the object constructed in the videoconference and the needs declared by the subjects